Research into occupant’s motion in vehicles during crashes - Pelenyte‐Vyšniauskiene, Lina; Jurkauskas, Algirdas (Transport, 2005)
Traffic accidents depend on many factors and circumstances. Important data are registered by taking photos of the accident place, measuring the deformations of vehicles and skidding and sliding traces. Weather conditions, drivers’ and pedestrian’s actions are also taken into account. However the existing data are far from sufficient to conduct a research into traffic accidents. In such cases mathematical modelling and the application of computer programs are very helpful. This article deals with the processes during the collision of vehicles as well as the occupant’s dynamics inside the vehicle. The research studies on what the occupant motion depends and what is the power balance between the occupant and safety means. The article offers a way of evaluating injuries, measuring the occupants’ acceleration and velocity, taking into account different distances inside the vehicle during an accident. First Published Online: 27 Oct 2010